PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA - Cahyani Nuswandari (Jurnal Bisnis dan Ekonomi, 2009)
This study purposes to investigate affect corporate governance to corporateperformance. The analysis employed two kinds of models, first model with ROE asoperational performance measurement and second model with Tobin’s Q as marketperformance measurement.This study employs a multiple regression to test that corporate governancepositively significant affect corporate performance. The rating of CGPI by IICG is usedto measure to the corporate governance implementation. Sample of this study arecompanies that listed in Bursa Efek Jakarta, now Bursa Efek Indonesia and follow CGPIprogram. Amount of sample are 101 companies as a pooled data from 2001 to 2005.Secondary data is used in this study.The analysis shows that CGPI positively significant affect operationalperformance but CGPI doesn’t affect market performance. It maybe market does notrespond the implementation of corporate governance immediately. The affect can be seenfor long period because related with investor trust.Key words: corporate governance, performance, ROE, Tobin’s Q.